2008
DOI: 10.1084/jem.20071474
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate mediates platelet activation through the AMPA receptor

Abstract: Glutamate is an excitatory neurotransmitter that binds to the kainate receptor, the N-methyl-D-aspartate (NMDA) receptor, and the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor (AMPAR). Each receptor was first characterized and cloned in the central nervous system (CNS). Glutamate is also present in the periphery, and glutamate receptors have been identified in nonneuronal tissues, including bone, heart, kidney, pancreas, and platelets. Platelets play a central role in normal thrombos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 48 publications
0
74
1
Order By: Relevance
“…Our previous studies demonstrated that glutamate pre-treatment increased agonist induced platelet activation 1. Glutamate by itself does not directly alter the expression of surface markers of platelet activation, such as GPIIb/IIIa activation (PAC-1 antibody binding) and P-selectin expression1.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous studies demonstrated that glutamate pre-treatment increased agonist induced platelet activation 1. Glutamate by itself does not directly alter the expression of surface markers of platelet activation, such as GPIIb/IIIa activation (PAC-1 antibody binding) and P-selectin expression1.…”
Section: Resultsmentioning
confidence: 97%
“…Most peripheral glutamate receptors when cloned and sequenced are identical to those of the CNS 7. We have previously demonstrated using a real time glutamate sensitive enzymatic probe that glutamate reaches very high concentrations (greater than 400 μM) within a developing thrombus1. We have also demonstrated that glutamate signaling has an important role in efficient thrombus formation by amplifying platelet activation, in part through platelet expressed AMPA receptors 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They express a broad range of neurotransmitter receptors and transporters (17). Therefore, it is not surprising that platelets have been extensively used to examine the functional properties of receptors and transporter activities (see Neurotransmission).…”
Section: Available Types Of Peripheral Samplesmentioning
confidence: 99%
“…The AMPAR subtype iGluRs exhibit kinetics at the millisecond timescale, and mediate fast neurotransmission in excitatory synapses, directly impacting synaptic plasticity, learning, and memory (1). Aberrations in AMPAR function are implicated in a wide range of diseases, from developmental diseases such as Fragile-X syndrome (3), to psychiatric disorders (1), acute trauma in ischemic stroke (4, 5), epileptic seizures (6, 7) and chronic neurodegenerative disorders such as Parkinson’s and Alzheimer’s diseases (1). …”
mentioning
confidence: 99%